People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 2014 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report, 2014)
This 2014 Article IV Consultation highlights that Hong Kong Special Administrative Region's (HKSAR) growth recovered to 2.9 percent in 2013 as resilient domestic demand helped offset the continued drag from net exports. As the global recovery takes hold, external demand is forecast to improve and lift growth to about 3 3/4 percent in 2014, although domestic demand remains solid. Inflation is expected to remain at about 4 percent, given the slow pass-through of housing costs. In line with the improved economic outlook, the 2014/15 budget includes a reduction in one-off measures of about 1.9 percent of GDP.